TRAINING SHORT STORY WRITING FOR MASS MEDIA IN THE MIDDLE SCHOOL OF BUDI AGUNG - Faudunasokhi Telaumbanua; Salam Irianto Nadeak (Jurnal Ilmiah Publipreneur, 2019)
Literacy cannot be separated from the world of education. Literacy refers to the ability to solve problems and achieve life goals by using text as the primary medium, orally, and in writing. Literacy activities are part of the character education process through reading and writing skills. This means that character education can be obtained through reading and writing, for example, short stories. By reading and writing short stories, it is hoped that Indonesian students will be nurtured to become religious, integrity, nationalist, independent, and have cooperation. Besides, short stories that have been written can be sent to the mass media and become one of the coffers of income for students. On this basis, this community service proposal is aimed at developing a culture of literacy among students as well as building an entrepreneurial spirit by sending short stories to mass media